Konsep Gender Perspektif Hukum Islam - Fatmawati Fatmawati (Universitas Pangeran Diponegoro Nganjuk, 2024)
The concept of gender in Islamic perspective emphasizes balance and justice between men and women. Islam teaches that both have equal roles and responsibilities in various aspects of life, including worship, social, economic, and political spheres. Despite biological differences, Islam underscores that a person's status is determined by their piety and deeds, not by their gender. This article explores the concept of gender in Islam, interpretations of sacred texts related to gender, and their implications in modern life. Using normative and contextual analysis approaches, the article also examines how Islamic teachings provide space for women's empowerment without violating the principles of Sharia. Furthermore, it discusses the challenges and opportunities in achieving gender equality in an increasingly complex society, offering new perspectives on understanding gender issues from an Islamic viewpoint.